Unravelling the dorsal periaqueductal grey matter NMDA receptors relevance in the nitric oxide-mediated panic‑like behaviour and defensive antinociception organised by the anterior hypothalamus of male mice - Falconi-Sobrinho, Luiz Luciano; dos Anjos-Garcia, Tayllon; Hernandes, Paloma Molina [UNESP]; Rodrigues, Bruno Mangili de Paula; Almada, Rafael Carvalho [UNESP]; Coimbra, Norberto Cysne (Springer Nature, 2023)
Rationale: Previous studies suggested that the dorsal column of the periaqueductal grey matter (dPAG) can be a target of neural pathways from hypothalamic nuclei involved in triggering fear-related defensive responses. In turn, evidence is provided suggesting that microinjection of the nitric oxide (NO) donor SIN-1 into the anterior hypothalamus (AH) of mice evokes panic-like behaviours and fear-induced antinociception. However, it is unknown whether the dPAG of mice mediates these latter defensive responses organised by AH neurons. Objectives: This study was designed to examine the role of dPAG in mediating SIN-1-evoked fear-induced defensive behavioural and antinociceptive responses organised in the AH of mice. Methods: First, neural tract tracing was performed to characterise the AH-dPAG pathways. Then, using neuropharmacological approaches, we evaluated the effects of dPAG pretreatment with either the non-selective synaptic blocker cobalt chloride (CoCl2; 1 mM/0.1 μL) or the competitive N-methyl-d-aspartate (NMDA) receptor antagonist LY235959 (0.1 nmol/0.1 μL) on defensive behaviours and antinociception induced by microinjections of SIN-1 in the AH of male C57BL/6 mice. Results: AlexaFluor488-conjugated dextran-labelled axonal fibres from AH neurons were identified in both dorsomedial and dorsolateral PAG columns. Furthermore, we showed that pre-treatment of the dPAG with either CoCl2 or LY235959 inhibited freezing and impaired oriented escape and antinociception induced by infusions of SIN-1 into the AH. Conclusions: These findings suggest that the panic-like freezing and oriented escape defensive behaviours, and fear-induced antinociception elicited by intra-AH microinjections of SIN-1 depend on the activation of dPAG NMDA receptors.
Keywords: Anterior hypothalamus; Defensive behaviour; Fear-induced analgesia; Nitric oxide; NMDA receptors; Periaqueductal grey matter; Stress